Why Maximize Expected Choice‐Worthiness?. (14th July 2018) - MacAskill, William; Ord, Toby
Abstract: This paper argues in favor of a particular account of decision‐making under normative uncertainty: that, when it is possible to do so, one should maximize expected choice‐worthiness . Though this position has been often suggested in the literature and is often taken to be the 'default' view, it has so far received little in the way of positive argument in its favor. After dealing with some preliminaries and giving the basic motivation for taking normative uncertainty into account in our decision‐making, we consider and provide new arguments against two rival accounts that have been offered—the accounts that we call 'My Favorite Theory' and 'My Favorite Option'. We then give a novel argument for comparativism —the view that, under normative uncertainty, one should take into account both probabilities of different theories and magnitudes of choice‐worthiness. Finally, we further argue in favor of maximizing expected choice‐worthiness and consider and respond to five objections.